Use of hiPSC-Derived Cardiomyocytes to Rule Out Proarrhythmic Effects of Drugs: The Case of Hydroxychloroquine in COVID-19 - Sala, Luca; Leonov, Vladislav; Mura, Manuela; Giannetti, Federica; Khudiakov, Aleksandr; Moretti, Alessandra; Crotti, Lia; Gnecchi, Massimiliano; Schwartz, Peter J. (Frontiers in Physiology, 2022)
In the early phases of the COVID-19 pandemic, drug repurposing was widely used to identify compounds that could improve the prognosis of symptomatic patients infected by SARS-CoV-2. Hydroxychloroquine (HCQ) was one of the first drugs used to treat COVID-19 due to its supposed capacity of inhibiting SARS-CoV-2 infection and replication in vitro. While its efficacy is debated, HCQ has been associated with QT interval prolongation and potentially Torsades de Pointes, especially in patients predisposed to developing drug-induced Long QT Syndrome (LQTS) as silent carriers of variants associated with congenital LQTS. If confirmed, these effects represent a limitation to the at-home use of HCQ for COVID-19 infection as adequate ECG monitoring is challenging. We investigated the proarrhythmic profile of HCQ with Multi-Electrode Arrays after exposure of human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) from two healthy donors, one asymptomatic and two symptomatic LQTS patients. We demonstrated that: I) HCQ induced a concentration-dependent Field Potential Duration (FPD) prolongation and halted the beating at high concentration due to the combined effect of HCQ on multiple ion currents. II) hiPSC-CMs from healthy or asymptomatic carriers tolerated higher concentrations of HCQ and showed lower susceptibility to HCQ-induced electrical abnormalities regardless of baseline FPD. These findings agree with the clinical safety records of HCQ and demonstrated that hiPSC-CMs potentially discriminates symptomatic vs asymptomatic mutation carriers through pharmacological interventions. Disease-specific cohorts of hiPSC-CMs may be a valid preliminary addition to assess drug safety in vulnerable populations, offering rapid preclinical results with valuable translational relevance for precision medicine.